Pengaruh E-Commerce, Motivasi Berwirausaha, Dan Lingkungan Keluarga Terhadap Minat Berwirausaha (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Metro) - Durotun Nasikah; Nani Septiana; Fatma Kumala (Universitas Muhammadiyah Metro, 2024)
The Central Statistics Agency (BPS) recorded the open unemployment rate (TPT) in Indonesia at 5.83% in February 2022. The average from college when graduating is more prepared to find a job not to create jobs, prospective graduates from universities are more prepared for the selection of new employees both from government agencies and from private companies, rather than preparing to open job opportunities by entrepreneurship. Therefore, it is necessary to cultivate the entrepreneurial spirit of students because by having an entrepreneurial spirit, it is hoped that students can create jobs or entrepreneurship after graduating from college. The purpose of this study is to find out whether e-commerce affects entrepreneurial interest, and to find out whether entrepreneurial motivation affects entrepreneurial interest, and to find out whether family environment affects entrepreneurial interest. The sample of this study was the Management class of 2019 Universitas Muhammadiyah Metro as many as 50 students with sampling techniques using Accidental Sampling. Data were collected through questionnaires, and data analysis using Validity Test, Reliability Test, Normality Test, Linearity Test, Homogeneity Test, Multiple Linear Regression Analysis, T Test, F Test, Determination Coefficient Test, Statistical Hypothesis using the program (SPSS 25). The results showed that there is a positive and significant influence of e-commerce on entrepreneurial interest, there is a positive and significant influence of entrepreneurial motivation on entrepreneurial interest, there is a positive and significant influence of the family environment on entrepreneurial interest Keywords: E-commerce, Entrepreneurial Mobility, Family Environment, Entrepreneurial Interest